The Relationship between Instructional Leadership, Understanding of Tri Kaya Parisudha Values, Work Motivation, and Work Commitment on Teacher Performance - Komang Budiad; Ni Luh Gede Erni Sulindawati; Basilius Redan Werang (Universitas Pendidikan Ganesha, 2026)
Teacher performance in instructional implementation continues to face challenges in the areas of planning, execution, and evaluation, which in turn affect overall educational quality. This study aims to analyze the relationships between principals’ instructional leadership, teachers’ understanding of the Tri Kaya Parisudha values, work motivation, and work commitment with teacher performance. A quantitative approach employing an ex post facto research design was adopted, involving 103 teachers as research participants. Data were collected through validated and reliable questionnaires and analyzed using multiple linear regression techniques. The results indicate that, both partially and simultaneously, instructional leadership, understanding of Tri Kaya Parisudha values, work motivation, and work commitment demonstrate significant and strong relationships with teacher performance. Each independent variable remained significantly associated with teacher performance after controlling for the effects of other predictors. The highest partial correlations were observed for instructional leadership and understanding of Tri Kaya Parisudha values, underscoring their substantial independent contributions to explaining variations in teacher performance. These findings highlight the strategic importance of strengthening value-based leadership rooted in local wisdom, enhancing teacher motivation, and fostering professional commitment as key pathways to improving teacher performance. The study offers practical implications for schools in designing sustainable teacher development programs oriented toward values-based leadership and continuous improvement of instructional quality.